Hubungan Karakteristik Penderita Tuberkulosis Paru dengan Hasil Pemeriksaan Tes Cepat Molekuler (TCM) - Siti Rimayah; Heni Muflihah; Tety H Rahim (Bandung Conference Series: Medical Science, 2023)
Abstract. Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis (MTB). The spread of MTB through the air is related to people's activities according to age, gender and occupation. The diagnosis of TB is currently enforced by the Molecular Rapid Test (TCM) method which replaces the microscopic examination of Acid-Fast Bacilli (AFB). The purpose of this study was to determine the relationship between the characteristics of pulmonary TB sufferers and the results of the TCM examination. This research is an analytic observational using secondary data. The subjects of this study were pulmonary TB patients at the Kertasemaya Health Center in the period January 2020 to December 2022. The research data included age, gender, occupation and TCM results. Analysis of the relationship between variables using the Chi-square test. A total of 100 subjects who met the inclusion criteria were patients diagnosed with pulmonary TB, the characteristics and results of TCM were recorded in medical records, and the age of the patient was over 15 years. The main characteristics of pulmonary TB sufferers are productive age (15-50 years) totaling 70 people (70%), male gender numbering 64 people (64%) and the majority not working totaling 57 people (57%). There was no relationship between age and TCM results (p=0.571), gender and TCM results (p=0.546), and occupation and TCM results (p=1.000). The conclusion of this study is that there is no relationship between age, gender, and occupation with the TCM examination results in pulmonary TB patients. Keywords: Age, Gender, Occupation, Pulmonary TB, TCM Abstrak. Tuberkulosis (TB) merupakan penyakit yang disebabkan Mycobacterium tuberculosis (MTB). Penyebaran MTB melalui udara berkaitan dengan aktivitas orang sesuai dengan usia, jenis kelamin, dan pekerjaan. Diagnosis TB saat ini ditegakkan dengan metode Test Cepat Molekuler (TCM) yang menggantikan pemeriksaan mikroskopik Basil Tahan Asam (BTA). Tujuan penelitian ini yaitu untuk mengetahui hubungan karakteristik penderita TB Paru dengan hasil pemeriksaan TCM. Penelitian merupakan observasional analitik menggunakan data sekunder. Subjek penelitian ini adalah pasien TB Paru di Puskesmas Kertasemaya pada periode Januari 2020 sampai Desember 2022. Data penelitian meliputi usia, jenis kelamin, pekerjaan serta hasil TCM. Analisis hubungan antar variabel menggunakan uji Chi-square. Total subjek berjumlah 100 orang yang memiliki kriteria inklusi yaitu pasien terdiagnosis TB Paru, Karakteristik dan hasil TCM tercatat rekam medis, dan usia penderita di atas 15 tahun. Karakteristik utama penderita TB Paru adalah berusia produktif (15 – 50 tahun) berjumlah 70 orang (70%), jenis kelamin laki – laki berjumlah 64 orang (64%) dan mayoritas tidak bekerja berjumlah 57 orang (57%). Tidak ada hubungan antara usia dengan hasil TCM (p=0,571), jenis kelamin dengan hasil TCM (p=0,546), dan pekerjaan dengan hasil TCM (p=1,000). Kesimpulan penelitian ini adalah tidak terdapat hubungan antara usia, jenis kelamin, dan pekerjaan dengan hasil pemeriksaan TCM pada penderita TB paru. Kata Kunci: Jenis Kelamin, Pekerjaan, TCM, TB Paru, Usia